Effects of vitamin D on the prevention and treatment of COVID 19: a systematic review (Research, Society and Development, 2020)
Introduction: Currently, the world has faced one of the largest pandemies with SARS-CoV-2, which causes the COVID-19 disease. It is notorious that its clinical spectrum has a wide variation, ranging from asymptomatic infections to severe conditions. Among some potential factors being correlated by research with infection and disease severity is vitamin D. Thus, the present study aims to understand the effects of vitamin D on the prevention and treatment of COVID-19. Methods: A systematic review of the literature was conducted in the PubMed, Cochrane and Scielo databases, based on articles published in 2019 and 2020. Of the 319 articles identified, 7 were selected from observational studies and one clinical trial. Results: Few studies are available to date, and studies have brought controversial results, since observational studies have associated that low vitamin D levels could interfere with the prevention and severity of the disease, but others have not observed associations. Conclusion: There is still no scientific basis for establishing a causal relationship between vitamin D levels and SARS-CoV-2 infection, whether in prevention, treatment or mortality. Therefore, further studies are needed to understand how these factors interact.